Analisis Pemasaran Kopra di Desa Jiko Kecamatan Motongkad Kabupaten Bolaang Mongondow Timur - Puasa, Grassela Noviti; Rumagit, Grace Adonia Josephine; Sendow, Martha Mareyke (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2023)
This study aims to analyze marketing channels, analyze marketing margins, and analyze farmer's share in each copra marketing channel in Jiko Village. Data collection using purposive sampling method, namely the determination of respondents intentionally for a sample of farmers who want to be interviewed, in this study the sample taken was 15 respondents, consisting of a sample of farmers 10 respondents, a sample of village intermediary traders 3 respondents, and sub-district intermediary traders 2 respondents using the snowball sampling method. The results of this study show that the copra marketing channel in Jiko Village, Motongkad District, East Bolaang Mongondow Regency has 2 marketing channels. It can be concluded that marketing channel 1 consists of: farmers - intermediary traders - factories. And marketing costs are transportation costs, packaging, labor, and retribution with a total cost of Rp.823.2 Marketing channel 2 consists of farmers - district intermediaries - factories. And marketing costs are transportation costs, packaging, labor, and retribution, with an overall total cost of Rp.1,449.8 copra marketing efficiency can be seen from the marketing margins of channels I and II of Rp.3000. for farmer share channel 1 with II Rp.62.5 with a percentage of 50% in each channel. And we can see these two channels are very efficient because for village traders and pecamatan traders have the same purchase price and selling price in each channel.